1986
DOI: 10.1111/j.1432-1033.1986.tb09492.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic synthesis of isoflavones

Abstract: The NADPH and oxygen-dependent conversion of (2 S)-naringenin to genistein catalyzed by a microsomal preparation from elicitor-treated soybean cell suspension cultures has been resolved into two steps. In the first step (2s)-naringenin is converted to a product (P-2) which yields genistein in a second step. The chemical behaviour of P-2 and its ultraviolet and mass spectral data are consistent with a 2-hydroxyisoflavanone structure. The conversion of (2 S)-naringenin to P-2 requires NADPH, oxygen and cytochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(71 citation statements)
references
References 24 publications
4
65
0
Order By: Relevance
“…IFS, which is used to prepare 2,7,49-trihydroxyisoflavanone, was previously shown to accept only 2S-flavanones as substrates (Hagmann and Grisebach, 1984;Kochs and Grisebach, 1986). Consistently, our studies here also demonstrated that the recombinant M. truncatula IFS only converted 2S-liquiritigenin (a 2S-flavanone) into 2,7,49-trihydroxyisoflavanone when incubated with a racemic mixture of flavanone substrates (data not shown).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…IFS, which is used to prepare 2,7,49-trihydroxyisoflavanone, was previously shown to accept only 2S-flavanones as substrates (Hagmann and Grisebach, 1984;Kochs and Grisebach, 1986). Consistently, our studies here also demonstrated that the recombinant M. truncatula IFS only converted 2S-liquiritigenin (a 2S-flavanone) into 2,7,49-trihydroxyisoflavanone when incubated with a racemic mixture of flavanone substrates (data not shown).…”
Section: Discussionsupporting
confidence: 76%
“…To obtain the hydroxyisoflavanone substrate that is not commercially available and is chemically unstable, 2,7,49-trihydroxyisoflavanone was prepared biosynthetically using recombinant M. truncatula IFS incubated with a racemic mixture of 2R/2S-liquiritigenin (7,49-dihydroxyflavanone) substrates (Figure 1). In this reaction, only the 2S-isomer served as an IFS substrate (data not shown), consistent with previous reports of IFS substrate specificity (Hagmann and Grisebach, 1984;Kochs and Grisebach, 1986). However, the 2,7,49-trihydroxyisoflavanone product resulting from this IFS-catalyzed in vitro reaction existed as a pair of stereoisomers based upon rapid purification using chiral HPLC (data not shown).…”
Section: -O-methylation Of Pterocarpans and Functional Identificatiosupporting
confidence: 79%
“…Several hypotheses were proposed for the reaction mechanism of this oxidative 1,2-aryl migration reaction [6]. Kochs and Grisebach reported the isolation of 2-hydroxyisoflavanone as an intermediate in isoflavone synthesis by microsomes from elicitor challenged soybean cells, and proposed a mechanism which involves an enol epoxide of flavanone as a reaction intermediate [3,4]. Crombie et al suggested another mechanism in which epoxidation occurred on the side phenyl group of flavanone [7].…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…Selective pathway activation was demonstrated by a comparative lack of [ 13 C 9 ]isotope incorporation into flavones and flavonol. This metabolic regulation is likely controlled by the activation of key enzymes in isoflavone biosynthesis, namely 2-hydroxyisoflavanone synthase (IFS) (Hashim et al 1990;Kochs and Grisebach 1986) and 2-hydroxyisoflavanone dehydrogenase (HID) (Hakamatsuka et al 1998) (Fig. 6).…”
Section: Controlmentioning
confidence: 99%